Analisis Kualitas ISO 25010 Aplikasi Artificial Intelligence Troubleshooting Komputer dengan FURPS - Septriyan Anugrah; Andri Eka Putra (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
Artificial Intellegent Application Computer Troubleshooting is an application developed with the aim of being a tool to understand the damage to the computer. The method used in this test is ISO 25010 on the FURPS concept. The results show that the internal quality of this application has been achieved by meeting the requirements of FURPS. Keyword ISO 25010; Quality Analysis; Artificial Intellegent Aplication; Computer Troubleshooting; FURPS